Metagenomics reveals structural and functional gut mycobiota dysbiosis in Tibetan subjects with coronary heart disease - Cheng, Qi; Zhang, Liangzhi; Liu, Fengyun; Fan, Chao; Wu, Tianyi; Li, Yuan; Hou, Haiwen; Ma, Yan; Tan, Yueqing; Li, Yuxian; Hai, Yue; Zhang, Yanming (Human gene (Amsterdam, Netherlands), 2023)
Gut mycobiota play indispensable roles in human health. However, little is known about the alterations to gut mycobiota and their correlations with coronary heart disease (CHD) in Tibetan subjects. We conducted a study based on shotgun metagenomic sequencing of DNA extracted from faecal samples to analyse the taxonomic composition and functional annotation of the gut mycobiota of 14 CHD patients, 13 patients with non-stenosis coronary heart disease (NCHD), and 18 healthy controls (HT). The TMAO, creatinine, and TG levels of the CHD group were significantly higher than HT. The alpha-diversity indices, including Richness, Shannon, Simpson, and beta diversity were significantly different between CHD and HT. The relative abundances of Anaeromyces robustus, Aspergillus taichungensis, Glomus cerebriforme, Monosporascus ibericus, and Ophiocordyceps sinensis significantly differed among the three groups. There were significant positive correlations between lipopolysaccharide (LPS) and several metabolic pathways, including thermogenesis, Alzheimer's disease, oxidative phosphorylation, Parkinson's disease, and cardiac muscle contraction. A redundancy analysis (RDA) revealed that LPS and body mass index (BMI) were strongly positively associated with CHD. The foregoing results demonstrated that gut mycobiota dysbiosis is an important mechanism in the development of CHD in Tibetan subjects.